Technostress and Student Well-Being in Islamic Boarding Schools: The Impact of Restricted Gadget Use on Academic Performance and Life Satisfaction - Silfiatul Ulumiyah; Mochamad Chandra Saputra; Budi Darma Setiawan (Faculty of Computer Science (FILKOM) Brawijaya University, 2025)
Some boarding schools prohibit the use of gadgets in daily life. Prohibition of the use of gadgets makes students unable to keep up with the development of existing information technology, so it can affect the ability of students to operate information technology related to their utilization of information technology. Students feel dissatisfied with their gadgets because they feel left too far behind with existing technological developments. This dissatisfaction affects individual motivation to accept the development of information technology, causing discomfort, stress, and even fear when dealing with information technology. The rapid growth of technology, but the lack of access for students, can lead to technostress. Technostress has five components: techno-overload, techno-invasion, techno-complexity, techno-insecurity, and techno-uncertainty. This study aims to determine the effect of limiting gadget use on technostress, which affects students' academic performance and life satisfaction. Statistical analysis using PLS-SEM was conducted in this study. Statistical results show that restrictions on gadget use can cause techno-complexity (51.7%) and techno-insecurity (14.5%) in students. However, techno-complexity and techno-insecurity do not affect students' academic performance. On the other hand, techno-insecurity affects the decrease in students' life satisfaction (21.7%) and academic performance (14.1%). Techno-uncertainty affects the reduction of students' academic performance (10.9%).